Newly translated proteins are substrates for ubiquitin, ISG15, and FAT10 - Spinnenhirn, Valentina; Bitzer, Annegret; Aichem, Annette; Groettrup, Marcus (My University, 2017)
The ubiquitin-like modifier, FAT10, is involved in proteasomal degradation and antigen processing. As ubiquitin and the ubiquitin-like modifier, ISG15, cotranslationally modify proteins, we investigated whether FAT10 could also be conjugated to newly synthesized proteins. Indeed, we found that nascent proteins are modified with FAT10, but not with the same preference for newly synthesized proteins as observed for ISG15. Our data show that puromycin-labeled polypeptides are strongly modified by ISG15 and less intensely by ubiquitin and FAT10. Nevertheless, conjugates of all three modifiers copurify with ribosomes. Taken together, we show that unlike ISG15, ubiquitin and FAT10 are conjugated to a similar degree to newly translated and pre-existing proteins.
Keywords: 570